2011
DOI: 10.1186/1471-2458-11-628
|View full text |Cite
|
Sign up to set email alerts
|

Violence witnessing, perpetrating and victimization in medellin, Colombia: a random population survey

Abstract: BackgroundThe burden of injury from violence and the costs attributable to violence are extremely high in Colombia. Despite a dramatic decline in homicides over the last ten years, homicide rate in Medellin, Colombia second largest city continues to rank among the highest of cities in Latin America. This study aims to estimate the prevalence and distribution of witnesses, victims and perpetrators of different forms of interpersonal violence in a representative sample of the general population in Medellin in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Exposure to physical violence between parents is universal and all of the available results are in agreement that at least one-third of children all around the world are exposed to IPV while they were growing up [15][16][17][18][19] and confirmed a high level of exposure. However; the current study indicated a higher rate than the past research in Iranian population.…”
Section: Related Factorssupporting
confidence: 60%
“…Exposure to physical violence between parents is universal and all of the available results are in agreement that at least one-third of children all around the world are exposed to IPV while they were growing up [15][16][17][18][19] and confirmed a high level of exposure. However; the current study indicated a higher rate than the past research in Iranian population.…”
Section: Related Factorssupporting
confidence: 60%
“…Besides this, quality control was done for 10% of digitalized surveys. To see more details about the methodology of this study, other publications can be consulted 5,34 .…”
Section: Methodsmentioning
confidence: 99%
“…For this analysis, was used the database from a population survey of Medellin and its metropolitan area carried out in 2007 was utilized 5 . It was a cross-sectional study to determine the prevalence of different forms of violence and risky behaviors, as well as factors associated with violence, coexistence, and other risky behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations